1999
DOI: 10.1046/j.1365-3059.1999.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for resistance to Diaporthe toxica in lupins by estimation of phomopsins and glucoseamine in individual plants

Abstract: Immunological and biochemical assays were developed for screening for resistance to Diaporthe toxica in individual plants of narrow‐leafed lupins (Lupinus angustifolius). The former was an enzyme‐linked immunosorbent assay (ELISA) for measuring phomopsin mycotoxins and the latter gave an estimation of glucoseamine in infected stem pieces. Stems of L. angustifolius seedlings were inoculated with conidia from D. toxica cultures and, as expected with this latent disease, remained symptomless for 21 days after ino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…For example, Nicotiana glauca Graham was identified as resistant to T. basicola and subsequently incorporated into a tobacco (N. tabacum) breeding program (Trojak-Goluch, 2005). In another germplasm screen, Gossypium arboreum L. PI 1415 was found to be resistant to T. basicola and subsequently incorporated into a diploid cotton-breeding program (Berbec and Berbec, 1976;Shankara and Cowling, 1999;Wheeler et al, 1999). Based on these reports, evaluating Daphne germplasm for resistance to DSDS, through controlled screens, is a reasonable approach to identify host plant resistance to this pathogen.…”
mentioning
confidence: 99%
“…For example, Nicotiana glauca Graham was identified as resistant to T. basicola and subsequently incorporated into a tobacco (N. tabacum) breeding program (Trojak-Goluch, 2005). In another germplasm screen, Gossypium arboreum L. PI 1415 was found to be resistant to T. basicola and subsequently incorporated into a diploid cotton-breeding program (Berbec and Berbec, 1976;Shankara and Cowling, 1999;Wheeler et al, 1999). Based on these reports, evaluating Daphne germplasm for resistance to DSDS, through controlled screens, is a reasonable approach to identify host plant resistance to this pathogen.…”
mentioning
confidence: 99%
“…The present study does not find a direct correlation of growth and toxin formation as growth (measured by numbers [CFU/g]) declined around day 7, but PHOA production was still increasing. Both Lanigan et al ( 1979 ) in liquid media, and Shankar et al ( 1999 ) in lupine plant parts taken from latently infected plants, also found that PHOA production by P. leptostromiformis , similarly to A. westerdijkiae ’s OTA production, did not correlate well with mycelium growth.…”
Section: Discussionmentioning
confidence: 94%
“…As well as displaying toxicity in mammalian species, phomopsin A has also been shown to have phytotoxic properties, presumably also due to its anti-microtubule action, and the phomopsins are likely to have evolved in some Phomopsis species to facilitate colonisation of host plants (Edgar, 2004). For example, resistance of lupin cultivars to colonisation by D. toxica correlated with the level of phomopsins found in lupin seedlings six days after inoculation with the fungus (Shankar et al, 1999). More than 60 species of Phomopsis are pathogenic on host plants of economic importance (Uecker, 1988).…”
Section: Chemistrymentioning
confidence: 99%